Mimikri dan Ambivalensi dalam Cerpen “Ruma Sekola yang Saya Impiken” Karya Kwee Tek Hoay - Sitti Hardianti (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2022)
This research discusses traces of colonialism resulting from the meeting of Dutch and Chinese cultures in the short story Ruma Sekolah yang Saye Impiken by Kwee Tek Hoay. The research focust to describe the colonial’s effects of the diaspora, mimicry and ambivalence carried out by the Chinese community. Methods of data collection used literature study with reading-note techniques, data analysis using descriptive methods. Homi K. Bhaba's postcolonial theory was used to analyze the diaspora, mimicry, and ambivalence that occurred in Chinese society. The results and discussion found that cultural contact between the colonial (Dutch) and the colonized (Chinese) resulted in traces of colonial diaspora, mimicry, and ambivalence carried out by the Chinese community. These colonial traces then gave birth to a new identity for the stronger Chinese community. The presence of characters in the narrative who carry out mimicry and ambivalence also becomes a form of their resistance to identity discourses built by the Dutch. Through this short story, the writer (Hoay) implicitly fought against the Dutch in Indonesian at that time.